2018
DOI: 10.3390/biology7010013
|View full text |Cite
|
Sign up to set email alerts
|

Odor Communication and Mate Choice in Rodents

Abstract: This paper details how chemical communication is affected by ecological challenges such as finding mates. I list several conditions that affect the decision to attract mates, the decision to respond to the signals of potential mates and how the response depends on context. These mate-choice decisions and their outcomes will depend on the life history constraints placed on individuals such as their fecundity, sex, lifespan, opportunities to mate in the future and age at senescence. Consequently, the sender’s de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 152 publications
(262 reference statements)
0
23
1
Order By: Relevance
“…Previous studies showed that the frequency of self‐grooming in rodents, such as ground squirrels and hedgehogs, is higher when they encounter odor from opposite‐sex conspecifics than when they encounter odor from same‐sex conspecifics (Brockie, ; Ferkin, ; Ferkin, Sorokin, & Johnston, ; Steiner, ; Yu et al, ). This is may be due to the possibility that self‐grooming is a means by which animals communicate with opposite sex and select mates (Achiraman et al, ; Ferkin, , ; Yu et al, ). Therefore, in general, animals respond more intensely to the odor from opposite sex (Ferkin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the frequency of self‐grooming in rodents, such as ground squirrels and hedgehogs, is higher when they encounter odor from opposite‐sex conspecifics than when they encounter odor from same‐sex conspecifics (Brockie, ; Ferkin, ; Ferkin, Sorokin, & Johnston, ; Steiner, ; Yu et al, ). This is may be due to the possibility that self‐grooming is a means by which animals communicate with opposite sex and select mates (Achiraman et al, ; Ferkin, , ; Yu et al, ). Therefore, in general, animals respond more intensely to the odor from opposite sex (Ferkin, ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence suggests that chemosensory cues can alone mediate several types of social recognition 48,49 , such as mate and kin recognition 25,[50][51][52][53][54] . In the case of familiarity recognition, the picture is less clear.…”
Section: Social Recognition By Chemosensory Cuesmentioning
confidence: 99%
“…While searching for mates, adult male meadow voles will likely enter both familiar and unfamiliar areas (Boonstra, Xia, & Pavone, 1993;Madison, 1980aMadison, , 1980b during their daily wanderings (Batzli, 1985). If they are to gain mating opportunities, male voles would need to attend to and recollect the scent marks of several potential mates, as well as their location and reproductive status (Ferkin, 2015(Ferkin, , 2018Ferkin, Combs, delBarco-Trillo, Pierce, & Franklin, 2008). Male meadow voles that can recall the location of a female's nest should achieve higher reproductive success because female meadow voles are more likely to mate with males that visit their nest often (Spritzer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These cues are able to communicate an assortment of information like territory ownership, social, reproductive, health and nutritional status, sex, age, species and enable recognition of individuals (Borelli et al., 2009; Doty, 1986; Eisenberg & Kleiman, 1972; Halpin, 1986; Johnson, 1973; Ralls, 1971). This information would be distinct and unique to that scent donor (Johnston, 2003; Thom & Hurst, 2004) and be individually discernible to the receiver (Ferkin, 2018; Ferkin & Johnston, 1995; Halpin, 1986). The receiver can use this information to discriminate scents based on individuality or grouping, such as kin‐non‐kin, neighbor–stranger, conspecific–heterospecific, colony‐non‐colony, and so on (Halpin, 1986; Johnston & delBarco‐Trillo, 2009).…”
Section: Introductionmentioning
confidence: 99%